A lysosome specific ratiometric fluorescent probe for detection of bisulfite ion based on hybrid coumarin-benzimidazolium compounds. (19th October 2020) - Zhao, Jiangdong; Huang, Liliang; Yan, Meiling; Qu, Yi; Feng, Huangdi; Sun, Yanhong
Abstract: Hybrid 2-(2-(7-(diethylamino)-2-oxo-2H-chromen-3-yl)vinyl)-1, 3-dimethyl-1H-benzo[ d ]imidazol-3-ium iodide compounds (LHZD-1 ∼ 3 ) were synthesized by Knoevenagel condensation reaction. Their structures were confirmed by 1 H NMR, 13 C NMR and HRMS spectroscopy. The fluorescence property of LHZD-1 ∼ 3 varied with the substituent groups such as -Br, -H and -OMe in the benzimidazolium skeleton. The probe LHZD-1 showed remarkable selectivity for the bisulfite ion over other common anions and biotins, which outputted the obvious color change in both absorption (462 nm to 400 nm) and emission (580 nm to 480 nm) spectra. The probe LHZD-1 showed the lysosome positioning action in Hela cells. This study not only provides a way for optimizing coumarin-benzimidazolium probes but also holds considerable promise in detection of bisulfite ion in organelles. Graphical Abstract: